Intramedullary Nailing of Experimental Femoral Midshaft Osteotomies in Cats with Biodegradable Rods of Polylactic Acid - Räihä, J. E.; Mero, M.; Morelius, M.; Rokkanen, P.; Törmälä, P. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Fracture repair by intramedullary support with one or several steel implants is a cheap and quick technique, especially suitable for simple femoral, tibial and humeral fractures in small animals. These implants, however, usually have to be removed due to their excessive rigidity causing migration or osteoporosis. The biodegradable implants of polylactic and polyglycolic acid available for fracture re-pair are usually too short to be used in the medullary canals of dogs and cats. A new extrusion technique has provided essentially unlimited length rods of left isomeric polylactic acid with strength values comparable to steel, but a stiffness modulus; close to bone.To test their use for intramedullary nailing such rods of diameter 1.1 and 2 mm were used to stack pin femoral osteotomies in four cats. Follow-up time was 24 weeks. All femurs healed, but with slight or moderate angulation or rotation and fair callus formation. Two had a bone loss defect at the lateral osteotomy line. Histology revealed minor foreign body reactions from the implants.This technique is being developed to involve only one implant with ability to prevent rotation and a stiffness of about 40 to 60 gigapascals (between bone and steel) to provide adequate initial stiffness before biodegrading.A new extrusion technique has enabled manufacturing of longer rods of totally biodegradable polylactic acid. These were tested for intramedullary use with a stack pinning technique in four cat femurs. All osteotomies healed with fair callus formation and slight or moderate deviations or rotations. Two femurs had a bone loss defect at the lateral osteotomy line. Histology revealed good tolerance to the foreign material.
Keywords: Intramedullary stack pinning; biodegradable implants; left isomeric polylactic acid